The Emotional Effects of Science Narratives: A Theoretical Framework - Helena Bilandzic; Susanne Kinnebrock; Magdalena Klingler (Media and Communication, 2020)
Stories have long been discussed as a tool to make science accessible to the public. The potential of stories to stimulate emotions in their audiences makes them an emotional communication strategy par excellence. While studies exist that test the effects of stories in science communication on the one hand and the effects of emotions on the other hand, there is no systematic elaboration of the mechanisms through which stories in science communication evoke emotions and how these emotions influence outcomes such as knowledge gain and attitude change. In this article, we develop a theoretical framework of the “Emotional Effects of Science Narratives” (EESN-Model), which includes a typology of emotions likely to arise from reading science communication as well as mechanisms for each of the emotions to evoke the (desired) outcomes. The model serves as a heuristic to delineate the emotional effects of narratives in science coverage and will help guide research in this domain to provide a deeper understanding of the role of emotion in science news.